PENEGAKAN HUKUM BAGI PELAKU TINDAK BULLYING DI KALANGAN PESERTA DIDIK - Latifah, Siti (TAHKIM, 2024)
Violence against children causes trauma and injuries that endanger the physical and mental health of children, victims of bullying. This article aims to examine the factors that cause widespread bullying among students in schools, as well as law enforcement efforts against perpetrators of bullying in schools. The research results show that the general causes of bullying among students are family, social media and peers or the environment. Other factors causing bullying are due to ethnic differences, resistance to several groups, differences in physical condition, as well as economic and family background. Perpetrators of bullying against children are given criminal sanctions and diversion in accordance with the provisions of Law Number 35 of 2014 concerning Amendments to Law Number 23 of 2002 concerning Child Protection so as to provide a deterrent effect to perpetrators and protect other children from acts of bullying.. Key words: law enforcement, bullies, students, children